A39 CULTURE-ENRICHED METAGENOMICS REVEALED MICROBIAL ENGRAFTMENT FOLLOWING FMT IN PATIENTS WITH ULCERATIVE COLITIS. (4th March 2021) - Shekarriz, S; Whelan, F; Lau, J; Libertucci, J; Moayyedi, P; Surette, M
Abstract: NOT PUBLISHED AT AUTHOR'S REQUEST Funding Agencies: CIHRImagine SPOR